Utilization of sludge from ready-mixed concrete plants as a substitute for limestone fillers. (1st June 2016) - Audo, Mariane; Mahieux, Pierre-Yves; Turcry, Philippe
Highlights: Environmental impacts of sludge coming from ready-mixed concrete plants. Substitution of limestone fillers by sludge coming-from ready-mixed concrete plants in mortars formulation. Mechanical characterization of mortars made with sludge coming from ready-mixed concrete plants. Abstract: This study deals with the incorporation of sludge coming from ready-mixed concrete plants into mortars. Preliminary environmental investigations, made through leaching tests, showed the importance of managing those waste as they can be potentially pollutant regarding to their arsenic and chromium contents. Thus, management of the sludge can be environmentally and economically difficult. Reincorporation of those sludge into a closed loop concrete production is of particular interest. Also, it represents an interesting way to save raw materials (water, sand and limestone fillers). Yet, two main disadvantages were observed when using those sludge as limestone fillers substitute: – a decrease in the workability of the fresh state mortar, calling for a higher superplasticizer content; – a variability in the compressive strength of the hardened state mortars, between −30% and +17% when comparing to a reference mortar.